COMMUNITY SOCIAL CAPITAL AS A STRATEGY TO REDUCE THE RISK OF FLOOD DISASTERS IN PELALAWAN REGENCY - Rina Susanti; Achmaf Hidir; Yoskar Kadarisman; Teguh Widodo; Risdayati; Mochammad Latif Amin (SOSIOEDUKASI, 2025)
Pelalawan Regency is one of the areas most severely affected by annual flooding in Riau Province, particularly Kuala Terusan Village located at the confluence the Kampar and Batang Nilo Rivers. Despite living in a physically vulnerable area with flood heights reaching 100-180 cm annually, the community choosesremain resilient. This study aims: first, to identify elements of social capital possessed by the watershed community in Kuala Terusan Village in facing annual floods; second, to analyze the role of social capital in enhancing community capacity to reduce risks and accelerate disaster management. Using a qualitative approach with case study design, data were collected through in-depth interviews, participatory observation, and focus group discussions with residents who have experienced repeated floods. The findings reveal that three dimensions of social capital social networks, collective norms and trust work synergistically as the community’s immune system. Social networks function as early warning systems through RT/RW structures, collective norms manifest in preventive mutual cooperation and collective economic strategies that transform floods into “blessings” through abundant fish catches, while high trust enables efficient asset security and aid distribution. This bottom-up strategy proves more adaptive rapid, and contextual in reducing flood risks compared to approaches solely relying on external interventions. This research contributes to expanding social capital theory in the context of recurring slow-onset disasters in rural river basin areas.